Past and present streams in international hospitality research - Lin, Naiqing; Ottenbacher, Michael (My University, 2020)
According to definition, modern hospitality management could be defined as classified business management based on six multidimensional core industry like restaurants, hotels, travel, attractions, conventions, and leisure with its constituent and relevant interdependent relationships. In this chapter, we reviewed the growth of international hospitality management, and the new emerged managerial challenges related to the research of international hospitality management. We also provided a brief review of history and summarized the current findings from empirical research related to research methodology and managerial problems. Nevertheless, this chapter serves as a brief introduction to the background, history, and challenges currently facing international hospitality management. This chapter will help guide readers to the relevant background and research topics about to come in the later chapters of this book. With an increased understanding of the multi-national business behavior, future hospitality managers will find the knowledge to embrace in an increasing difficult challenge and find scientific solutions in a complexing political, diversified social-cultural and legal systems.
Keywords: hospitality management; managerial problems; multi-national; hospitality industry; multidimensional core